Fort and Fortress in Indian Cinema: Study on the Role of Indian Historical Monuments on Indian Cinema - Kak, Sabzaar; Pundir, Ishita (International Journal of Psychosocial Rehabilitation, 2020)
The Indian monuments give out a very impressive reflection about the Indian culture, by which even today’s artists get inspired. These types of historical monuments preserve the memory of famous artworks. This also gives reference to the ancient rulers, their achievements, and their downfall. These monuments became historic and added to the record of man’s art workmanship. Indian Cinema, on the other side, in today’s world, is the most popular means of entertainment. Millions of people watch cinema every day all over the world not only as a means of entertainment but also as an escape from the monotony, boredom, anxiety, and troubles of life. The usage of monuments as film locations gives major highlight to the Indian masterpieces. This paper attempts to shed light on the role of monuments on Indian cinema and also, I would like to elaborate on the tradition and culture of Indian cinema with historic beauty by going through detail study on the subject written by distinguished authors